Magnetic properties of Ni-Fe nanowire arrays: effect of template material and deposition conditions - Aravamudhan, S; Singleton, J; Goddard, P; Bhansali, S (2009)
The objective of this work is to study the magnetic properties of arrays of Ni-Fe nanowires electrodeposited in different template materials such as porous silicon, polycarbonate and alumina. Magnetic properties were studied as a function of template material, applied magnetic field (parallel and perpendicular) during deposition, wire length, as well as magnetic field orientation during measurement. The results show that the application of magnetic field during deposition strongly influences the c-axis preferred orientation growth of the Ni-Fe nanowires. The samples with magnetic field perpendicular to the template plane during deposition exhibit strong perpendicular anisotropy with greatly enhanced coercivity and squareness ratio, particularly in the Ni-Fe nanowires deposited in polycarbonate templates. In the case of polycarbonate template, as magnetic field during deposition increases, both coercivity and squareness ratio also increase. The wire length dependence was also measured for polycarbonate templates. As wire length increases, coercivity and squareness ratio decrease, saturation field increases. Such magnetic behaviour (dependence on template material, magnetic field, wire length) can be qualitatively explained by preferential growth phenomena, dipolar interactions among nanowires and perpendicular shape anisotropy in individual nanowires. © 2009 IOP Publishing Ltd.